LIDERAZGO ESTRATÉGICO EN LA I.E. ADA A. BYRON Y SU IMPACTO EN FACTORES DEL CLIMA ORGANIZACIONAL, AÑO 2016 - CAMPOS SOBRINO, MARIANA ALEJANDRA (2016)
"Strategic leadership" in the I.E Ada A. Byron and its impact on the "factors of the organizational climate", year 2016; This investigative work, due to the turn of the object of analysis, has used the descriptive design, since it pursues the purpose of evidencing and dimensioning the impact index of strategic leadership on the factors of "organizational climate" in "strategic leadership" IE Ada A. Byron and its impact on the “factors of the organizational climate”, year 2016. According to the results analyzed in a reflective and proven way, it is concluded that "strategic leadership" has a relevant impact on the factors of the "organizational climate" in IE Ada A. Byron, during 2016, showing a positive correlation index of 0.914. Due to the aforementioned, focusing on the coefficient of variability (r2 = 0.835) we find that the variable “organizational climate” has an influence of 83.5% by Strategic Leadership, all of this analyzed from the perspective of EI respondents. Ada A. Byron, 2016. Keywords: Strategic leadership, Organizational climate factors.